1983
DOI: 10.1002/j.1939-4640.1983.tb00769.x
|View full text |Cite
|
Sign up to set email alerts
|

The Binding Patterns of Antisera to Sex Steroids and Human Gonadotropins on Human and Rhesus Monkey Spermatozoa

Abstract: The presence of different hormones on the surface of ejaculated spermatozoa was determined by immunofluorescence studies of the binding patterns of specific antisera to these hormones. There were striking similarities in the binding pattern of antisera to steroid hormones found on human and monkey spermatozoa. Assuming the intensity of fluorescence is proportional to the concentration of the hormone, concentrations of testosterone on the acrosomal and the postacrosomal regions were higher than levels of proges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Mac Leod (17) prescribed low dose of oral testosterone to his patients with normal count and low motility. Studies by Allag et al (18) supported Mac Leod by demonstrating testosterone receptors on spermatozoa. Study by Das (personal communications) showed that the spermatozoa that had less or no motility were with less number of receptors for testosterone.…”
Section: Discussionmentioning
confidence: 92%
“…Mac Leod (17) prescribed low dose of oral testosterone to his patients with normal count and low motility. Studies by Allag et al (18) supported Mac Leod by demonstrating testosterone receptors on spermatozoa. Study by Das (personal communications) showed that the spermatozoa that had less or no motility were with less number of receptors for testosterone.…”
Section: Discussionmentioning
confidence: 92%
“…The assessment of sperm function included (1) the assessment of various parameters of motility by time exposure photomicrography [ 151, (2) the assessment of the fertilizing ability by zona-free hamster ova penetration test [21], and (3) the assessment of the distribution of testosterone-binding sites by indirect immunofluorescent technique [3]. In addition to the measurements of velocity (V), amplitude of lateral head displacement (Ah), and calculation of progressive ratio (straight line distance/total distance traveled per second; PR), the degree of flagellar bending (a) was also measured at different points on the sperm track as reported by Serres et al [18], and the mean angle for each sperm was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Although the concentrations of the C-I9 steroids in seminal plasma are only IO% of those in blood plasma, concentrations of conjugated and unconjugated oestrogens are about 300% in seminal plasma compared to blood plasma (Claus er at, 1983(Claus er at, , 1985. As found in human semen (Allag et at, 1983), oestrogens in the boar are unspecifically bound to the sperm surface, and so oestrogen concentrations in whole semen are about 2-fold compared to seminal plasma (Claus et at, 1985). It is likely that spermatozoa act as a carrier protein because the major part of the oestrogens originates from the seminiferous tubules and accessory glands contribute only about 15% of the seminal oestrogens as shown by vasectomy (Claus et al, 1985).…”
Section: Seminal Oestrogens: a Peculiarity Of The Boarmentioning
confidence: 97%